Resolving inheritance disputes due to Munasakhah through the concept of Tabayyun and Ta’awun - Azzahra Atu Prabangso; Faradila Dwi Ayu Saskhia; Gusti Yosi Andri; Ismayana Ismayana; Rika Lailatus Solihah (Interdisciplinary Social Studies, 2024)
The delay in the distribution of inheritance from the perspective of Islamic law is one of the crucial issues because it can trigger various conflicts among heirs. The purpose of this study is to apply the concepts of Tabayyun and Ta'awun as a dispute resolution mechanism in the inheritance distribution that has been postponed for a long time in a non-litigation manner and is based on maqasid as-sharia. This research is important to provide understanding and knowledge about the delay in implementation of inheritance distribution which can trigger disputes and divide relationships in the family. The qualitative analysis method was used to obtain a more comprehensive understanding related to the resolution of inheritance disputes that occur due to the delay of the distribution or munasakhat. The results show that lack of understanding of fiqh of Islamic inheritance is a key factor causing disputes among families. The lack of clarity in the identification of the right heir is also a major factor triggering disputes among the families. In addition, the lack of knowledge of the udzur shari'i recognized in Islam can also cause conflicts among family members. The aim of this paper is to use the concept of Tabayyun and Ta’awun to resolve inheritance disputes. The study also discusses the role of religious leaders, such as ustadz or kyai, in maximizing the mediation stage at the court level in order to realize the principle of simple, fast, and low-cost justice as stipulated in the Judicial Power Law, potentially offering strategies to enhance the efficiency and cost-effectiveness of legal processes in inheritance dispute resolution.